Business model analysis using indicators of global competitiveness (Journal of Economic Research & Business Administration, 2016)
Sustainable economic growth in the country is possible through better management aimed at building efficient and innovative company business models. A business model is one of the new concepts of modern entrepreneurship and strategic management. Interest in the business models in the academic and research circles appeared in the middle of 1990s. Today analysis of business model components of Kazakhstan manufacturing companies and observing the dynamics of main indicators of the industry have become of special interest. The authors have examined business model components at the macro level using indicators included in the index of global competitiveness. It is noteworthy to say that existing methods of business model analysis can be used to analyze the activity of one, or to compare business models of two companies, however, their use at higher levels might not be appropriate. The importance of indicators of global competitiveness index is also due to the fact that they are the instrument of strategic management of the state economy and may help to achieve economic development and competitiveness for certain entities.
Keywords: business model; components of the business model; business model analysis at the macro level; competitiveness indicators.